Advanced Low Power Verification Methodologies: A Comprehensive Framework for Modern Semiconductor Design - Sharvani Mukkala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for low power verification in modern semiconductor designs, addressing the growing challenges in power management for AI, IoT, and mobile applications. The article explores advanced verification methodologies that combine power-aware simulations, formal verification techniques, and hybrid approaches to ensure robust power management implementation. The framework integrates multiple verification strategies, including power gating verification, clock domain crossing analysis, and dynamic power analysis under various workloads, providing a systematic approach to detecting power-related issues early in the design cycle. The methodology emphasizes the importance of mixed-signal simulations and logical equivalence checking across power modes, offering a complete verification solution for complex power architectures. The proposed approach demonstrates improved coverage of power-related scenarios while reducing verification effort through a strategic combination of simulation, emulation, and formal verification techniques. This article contributes to the field by presenting a unified verification strategy that addresses the complexities of modern power-aware designs while ensuring comprehensive verification closure.